The Impact of Undetected In Vitro Hemolysis or Sample Contamination on Patient Care and Outcomes in Point-of-Care Testing: A Retrospective Study. (22nd February 2020) - O'Hara, Matthew; Wheatley, Elizabeth G; Kazmierczak, Steven C
Abstract: Background: Point-of-care (POC) testing is an integral diagnostic component in clinical settings like the emergency department (ED). However, most POC testing devices are unable to detect endogenous interferents such as hemolysis, which typically occurs during sample collection and handling and can falsely increase measured potassium (pseudohyperkalemia), a phenomenon we hypothesized may significantly impact patient care. Methods: In this retrospective study, we evaluated 100 unique admissions to the Oregon Health & Science University ED, presenting with elevated potassium measured at the POC. To evaluate whether in vitro hemolysis had occurred, POC test results were compared to repeat testing of the original specimen, or other specimens tested within 90 minutes in the Core laboratory. Review of associated Electronic Health Records determined whether elevated potassium initially measured using the POC analyzer was real, or due to in vitro hemolysis or contamination, and whether pseudohyperkalemia impacted patient management or care. Results: Of the 100 admissions with hyperkalemia measured using a POC analyzer, 40% were found to have pseudohyperkalemia due to hemolysis or contamination. Of these 40 patients, 6 experienced repeated testing, and an additional 5 were noted to have altered patient management, specifically due to pseudohyperkalemia. Conclusions: This study demonstrates the incidence of in vitro hemolysis, which is unknown to the POC operator, is high in patients who show an elevated potassium as measured at the POC. Furthermore, in vitro hemolysis can significantly impact patient management, suggesting that minimizing the incidence of unrecognized hemolysis will benefit hospital efficiency, decrease waste, and improve patient care.